Synthesis, Kinetics and Mechanisms of Designer and Natural Product Antioxidants: From Solution to Cells - Li, Bo (Université d'Ottawa / University of Ottawa, 2016)
Lipid peroxidation has been implicated in the onset and progression of many degenerative diseases, including cardiovascular disease, Alzheimer’s disease and cancer. Accordingly, for more than 50 years, considerable effort has been devoted to the design of synthetic compounds or the discovery of natural products that can slow lipid peroxidation. Despite the enormous investments made to date, no clear antioxidant strategies have emerged for the treatment and/or prevention of degenerative disease. We argue that this is because of a lack of fundamental understanding of the chemical reactivity of these compounds in relevant contexts. Herein, we describe studies of our optimized synthetic radical-trapping antioxidant (RTA) – the tetrahydronaphthyridinols (THNs). We first present the synthesis of a series of THN analogs of α-tocopherol (Nature’s premier lipid-soluble radical-trapping antioxidant) with varying sidechain substitution and then demonstrate how systematic changes in the lipophilicity of these potent antioxidants impact their peroxyl radical-trapping activities in lipid bilayers and mammalian cell culture. Their regenerability by water-soluble reductants in lipid bilayers, binding to human tocopherol transport protein (hTTP), and cytotoxicity were also evaluated to provide insight on whether this type of antioxidant can be potentially pushed toward animal studies. We also describe analogous studies of natural products such as the garlic-derived thiosulfinate allicin and the grape-derived polyphenol resveratrol. These compounds have attracted significant attention in the past 20 years due to their purported health benefits, which are often ascribed to their purported radical-trapping activities. To date, systematic studies on their radical-trapping activities in solution, lipid bilayers and mammalian cells have been lacking. We have determined that allicin and petivericin, while effective RTAs in solution, are not so in lipid bilayers. Moreover, the compounds are not antioxidants in cell culture, but instead kill the cells. Similarly, resveratrol and its dimers pallidol and quadrangularin A, are found to be inefficient RTAs in lipid bilayers. Our studies to date rather suggest that they autoxidize readily to produce hydrogen peroxide, which may induce expression of phase 2 antioxidant enzymes, affording cytoprotection. Our insights underscore the need for systematic studies of antioxidant activity in multiple contexts.
Keywords: radical-trapping antioxidant; lipid peroxidation; kinetics; mechanism; method